Transient tunnel vision and altered consciousness after a single dose of ibuprofen. Issue 9 (September 2022) - Finsterer, Josef
Although neurological/ophthalmologic side effects including headache, vertigo, somnolence, paresthesia, optic neuritis, and optic neuropathy are listed as side effects in the medication guidelines for ibuprofen, transient tunnel vision and altered consciousness after a single dose of ibuprofen have not been reported. The patient was a 48-year-old man who experienced sudden-onset tunnel vision for a few seconds, followed by an altered state of consciousness for 20 minutes, during which he was communicating with his boss in an altered manner, 15 minutes after having taken 200 mg of ibuprofen. After awakening, he required 2 to 3 hours to return to his premorbid condition. No tongue biting or secessus occurred. Because his blood pressure, blood tests, blood gas analysis, electrocardiography, and electroencephalography results were normal and cerebral magnetic resonance imaging only showed non-specific spots in the subcortical white matter, the condition was attributed to ibuprofen. This case shows that a single dose of ibuprofen can cause severe side effects in the form of tunnel vision and altered consciousness. In some patients, single doses of ibuprofen may cause severe side effects.